Tissue antibodies in idiopathic autoimmune haemolytic anaemia - Blajchman, M. A. (1971)
Sera from patients with idiopathic autoimmune haemolytic anaemia (AIHA) were studied, by the immunofluorescent technique, for the presence of circulating organ-specific and non-organ-specific autoantibodies. In patients with warm AIHA there was an increased incidence in the non-organ-specific autoantibodies, compared to normal controls: In 15% of sera studied there were antinuclear antibodies detectable, and in 5% antimitochondrial antibodies were present. In cold AIHA, however, the frequency of these autoantibodies was not increased. The incidence of organ-specific autoantibodies was normal in both cold and warm AIHA. No correlation was found between the occurrence of these autoantibodies and pattern of serum immunoglobulin concentration, specific serological feature, or clinical manifestation. The significance of the increased incidence of tissue autoantibodies and their relation to autoimmune haemolytic anaemia remains to be elucidated, but in some way may be due to increased immunological reactivity.